A Survey of Adaptive and Real-Time Protocols Based on IEEE 802.15.4 - Feng Xia; Ruonan Hao; Yang Cao; Lei Xue (International Journal of Distributed Sensor Networks)
The IEEE 802.15.4 standard is a protocol that has been widely used in many applications exploiting wireless sensor networks (WSNs). However, it does not provide any means of differentiated services to improve the quality of service (QoS) for time-critical and delay-sensitive events. Furthermore, adaptive throughput performance for individual nodes cannot be supported with the current specifications. In this survey paper, we first discuss the negative aspects of IEEE 802.15.4 MAC in contention access period, contention-free period, and the overall cross-period, respectively, in terms of adaptive and real-time guarantees. We then give an overview on some interesting mechanisms used in existing adaptive and real-time protocols in compliance with IEEE 802.15.4. Careful examination of such research works reveals that by optimizing the original specifications and dynamically adjusting the protocol parameters, the total network efficiency can be significantly improved. Nevertheless, there are still certain challenges to overcome in pursuing the most appropriate protocol without introducing any unacceptable side effects.